The relative deficit of GDF15 in adolescent girls with PCOS can be changed into an abundance that reduces liver fat - Francis de Zegher (Nature Portfolio, 2021)
Abstract A prime concern of young patients with Polycystic Ovary Syndrome (PCOS) is the control of body adiposity, given their tendency to gain weight and/or their difficulty to lose weight. Circulating growth-and-differentiation factor-15 (GDF15) facilitates the control of body weight via receptors in the brainstem. C-reactive protein (CRP) and insulin are endogenous GDF15 secretagogues. We hypothesised that PCOS in non-obese adolescents is characterised by low concentrations of circulating GDF15, when judged by the degree of CRP and insulin drive. GDF15 was added as a post-hoc endpoint of two previously reported, randomised studies in non-obese adolescent girls with PCOS (N = 58; 60% normal weight; 40% overweight) who received either an oral oestroprogestogen contraceptive (OC), or a low-dose combination of spironolactone-pioglitazone-metformin (SPIOMET) for 1 year; subsequently, all girls remained untreated for 1 year. Adolescent girls with regular menses (N = 20) served as healthy controls. Circulating GDF15, CRP and fasting insulin were assessed prior to treatment, and halfway the on- and post-treatment years. Pre-treatment, the absolute GDF15 concentrations were normal in PCOS girls, but their relative levels were markedly low, in view of the augmented CRP and insulin drives. OC treatment was accompanied by a near-doubling of circulating GDF15 (on average, from 296 to 507 pg/mL) and CRP, so that the relative GDF15 levels remained low. SPIOMET treatment was accompanied by a 3.4-fold rise of circulating GDF15 (on average, from 308 to 1045 pg/mL) and by a concomitant lowering of CRP and insulin concentrations towards normal, so that the relative GDF15 levels became markedly abundant. Post-OC, the relatively low GDF15 levels persisted; post-SPIOMET, the circulating concentrations of GDF15, CRP and insulin were all normal. BMI remained stable in both treatment groups. Only SPIOMET was accompanied by a reduction of hepato-visceral fat (by MRI) towards normal. In conclusion, early PCOS was found to be characterised by a relative GDF15 deficit that may partly explain the difficulties that young patients experience to control their body adiposity. This relative GDF15 deficit persisted during and after OC treatment. In contrast, SPIOMET treatment was accompanied by an absolute and a relative abundance of GDF15, and followed by normal GDF15, CRP and insulin concentrations. The present findings strengthen the rationale to raise the concentrations of circulating GDF15 in early PCOS, for example with a SPIOMET-like intervention that attenuates low-grade inflammation, insulin resistance and ectopic adiposity, without necessarily lowering body weight. Clinical trial registries: ISRCTN29234515 and ISRCTN11062950.